Химия фтористых соединений актинидов - Тананаев И. В. Иван Владимирович; Николаев Н. С. Николай Сергеевич; Лукьянычев Ю. А. Юрий Алексеевич; Аленчикова И. Ф. Инна Феофилактовна (Москва, Изд-во АН СССР, 1963)
Исключено из фонда НТБ ТПУ